AKTIVASI ZEOLIT ALAM SEBAGAI ADSORBEN PADA ALAT PENGERING BERSUHU RENDAH - Laeli Kurniasari; Mohammad Djaeni; Aprilina Purbasari (Reaktor, 2011)
ACTIVATION OF NATURAL ZEOLITE AS AN ADSORBENT FOR LOW TEMPERATURE DRYING SYSTEM. Drying is one process which is used in many industries, especially in food product. The process usually still has low energy efficiency and can make food deterioration because of the usage of high temperature. One alternative in drying technology is the use of zeolite as a water vapor adsorbent. This kind of drying method make it possible to operate in lower temperature, hence it will be suitable for heat sensitive product. Natural zeolit can be one promising adsorbent since it is spreadly abundant in Indonesia. Natural zeolite must be activated first before used, in order to get zeolite with high adsorption capacity. Activation process in natural zeolite will change the Si/Al ratio, polarity, and affinity of zeolite toward water vapor and also increase the porosity. Activation of natural zeolite can be done with two methods, chemical activation use NaOH and physical activation use heat. In the activation using NaOH, natural zeolite is immersed with NaOH solution 0.5-2N in 2 hour with temperature range 60-900C. The process is continued with the drying of zeolite in oven with 1100C for 4 hours. While in heat treatment, zeolit is heated into 200-5000C in furnace for 2-5 hours. SEM analysis is used to compare the change in zeolite morphology before and after each treatment, while to know the adsorption capacity of zeolite, the analyses were done in many temperature and relative humidity. Result gives the best condition in NaOH activation is NaOH 1N and temperature 700C, with water vapor loading is 0.171 gr/gr adsorbent. In heat treatment, the best condition is 3000C and 3 hours with loading 0.137 gr water vapor/gr adsorbent.  Pengeringan merupakan salah satu proses yang banyak digunakan pada produk pangan. Proses ini umumnya menyebabkan kerusakan pada bahan pangan, disamping masih rendahnya efisiensi energi. Salah satu alternatif pada proses pengeringan yaitu penggunaan zeolit sebagai adsorben uap air. Proses pengeringan dengan menggunakan zeolit sebagai adsorben ini memungkinkan operasi pengeringan dilakukan pada suhu rendah sehingga sesuai untuk bahan yang tidak tahan panas. Zeolit alam merupakan salah satu alternatif bahan adsorben. Akan tetapi zeolit ini harus diaktivasi terlebih dahulu untuk mendapatkan zeolit dengan kemampuan adsorpsi yang tinggi. Proses aktivasi pada zeolit akan merubah rasio Si/Al zeolit, polaritas serta afinitas zeolit terhadap air dan meningkatkan pori-pori zeolit Adsorpsi zeolit alam dilakukan dengan dua cara yaitu dengan NaOH dan dengan panas. Pada aktivasi dengan NaOH, zeolit dicampur dengan NaOH 0,5-2N selama 2 jam pada suhu 60-900C. Sementara pada aktivasi fisis, zeolit dipanaskan pada 200-5000C selama 2-5 jam. Untuk mengetahui perubahan struktur pori zeolit maka dilakukan analisa SEM dan untuk mengetahui kemampuan adsorpsi zeolit maka dilakukan analisa daya adsorpsi zeolit terhadap uap air pada berbagai suhu dan berbagai kelembaban relatif. Hasil menujukkan bahwa pada aktivasi dengan NaOH diperoleh kondisi aktivasi terbaik adalah NaOH 1N pada pemanasan 700C dengan daya adsorpsi 0,171 gr uap air/gr adsorben. Sementara untuk aktivasi dengan panas, kondisi aktivasi terbaik adalah pemanasan 3000C selama 3 jam dengan daya adsorpsi 0,137 gr uap air/gr adsorben.